Amniotic membrane transplantation and conjunctival autograft combined with mitomycin C for the management of primary pterygium: A systematic review and meta-analysis - Taher, Nada Omar; Alnabihi, Ahmed Naji; Hersi, Reem Mahmoud; Alrajhi, Rawan Khalid; Alzahrani, Reham Ahmad; Batais, Waleed Talib; Mofti, Alaa Hesham; Alghamdi, Saeed Abdullah (Frontiers in Medicine, 2022)
Background: Pterygium is a common ocular surface disease. Recurrence is the greatest concern in the treatment of pterygium. Thus, a standardized and effective treatment modality with minimal risk for complications is needed for the management of pterygium. The aim of this systematic review and meta-analysis was to evaluate different tissue grafting options, including conjunctival autograft (CAG) with mitomycin C (MMC), CAG alone, and amniotic membrane transplantation (AMT), for the management of primary pterygium. Methods: We searched the MEDLINE, EMBASE, and CENTRAL databases for relevant studies. We included randomized controlled trials (RCTs) in which CAG+MMC and AMT were compared with surgical excision with CAG alone for the treatment of primary pterygium. The rates of recurrence and adverse events reported in the studies were also evaluated. Risk ratio (RR) was used to represent dichotomous outcomes. The data were pooled using the inverse variance weighting method. The quality of the evidence derived from the analysis was assessed using the Grading of Recommendations Assessment, Development, and Evaluation approach. Risk of bias was assessed using the revised Cochrane risk-of-bias tool for randomized trials. Results: Twelve RCTs (n=1144) were deemed eligible and included for analysis. Five RCTs had a low risk of bias, five had some concerns, and two had a high risk of bias. Subgroup analysis showed a statistically significant reduction in the rate of pterygium recurrence after CAG+MMC (RR=0.12; 95% confidence interval [CI], 0.02–0.63). There were insignificant differences between the rates of recurrence after AMT and CAG (RR=1.51; 95% CI, 0.63–3.65). Regarding adverse events, patients treated using AMT showed significantly lower rates of adverse events than those treated using CAG (RR=0.46; 95% CI, 0.22–0.95). CAG+MMC showed a safety profile comparable to that of surgical excision with CAG alone (RR = 1.81; 95% CI, 0.40–8.31). Conclusion: A single intraoperative topical application of 0.02% MMC during excision of pterygium followed by CAG significantly has shown to decrease the rate of pterygium recurrence to 1.4% with no severe complications.